Review on Vaidyaka Paribhasha Pradipa- A Comprehensive Treatise of Indian Pharmaceuticals by Govind Sen - Manjusha.B; S. A. Doddamani; Surekha. S. Medikeri; Anand Katti (International Journal of Ayurveda and Pharma Research, 2022)
Vaidyaka Paribhasha Pradipa was written by Govind Sen, son of Krishna Vallabh Sen. Vidyotini Hindi Tika was written by Indradev Tripathi. The book Vaidyaka Paribhasha Pradipa consists of almost all references collected from various Samhitas regarding the fundamental principles and different Ayurvedic herbal pharmaceutical preparations and descriptions on Panchakarma. The whole content of the book is divided into 4 Khandas. Prathama khanda deals with Mana paribhasha, Dravya samgrahana vidhi, and shelf life of different Kalpana etc. Dwitiya khanda deals with Panchavidha kashaya kalpana and its Upakalpana and dose. Tritiya khanda deals with Sneha kalpana, Sandhana kalpana and Paribhasha of different Gana. Chaturtha khanda deals with Panchakarma procedures and Sneha murchana. The present book review mainly focuses to highlight the framework of Vaidyaka Paribhasha Pradipa, provides information about the author, details of 4 Khandas, a special contribution to the field of pharmaceutical science by the author. Thus, Vaidyaka Paribhasha Pradipa, the compilation book on Bhaishajya Kalpana is a very essential and mandatory book for those who aspire to gain basic, clear, and thorough knowledge in Ayurvedic pharmaceuticals. It is one of the indispensable reference books. The present book is designed to help the young practitioners who prepare medicines and graduates and post-graduate scholars get a clear idea of medicine preparation.